Between Desire and Responsibility: Unplanned Pregnancies in Contemporary Romance Novels - Orsolya Barta; Ann Steiner (Journal of Popular Romance Studies)
The study investigates how unplanned pregnancy is presented and discussed in seven contemporary romance novels. Three main themes were identified: contraception, abortion, and the function of a pregnancy narrative. Within these subjects, we listed several examples with the support of interdisciplinary theories from gender studies, film theory, literary studies, medicine, sociology, and psychology. The topic is an outlier in the genre, but it still addresses many issues important to young women reading contemporary romance, e.g., the consequences of casual sex, contraception, abortion, responsibility, and motherhood. Now more than ever, the representation of young women experiencing unplanned pregnancies is a highly relevant theme of romance fiction. We observed that romance fiction responds to female fears and desires surrounding pregnancy and motherhood. Pregnancy in these stories is not simply a marketing trope for readers, but a vital part of the narrative, which induces the issues and complications that are presented in this study and relays particular aspects of women’s lives.